Carbon Monoxide Partially Mediates Protective Effect of Resveratrol Against UVB-Induced Oxidative Stress in Human Keratinocytes - Janice N. Averilla; Jisun Oh; Jong-Sang Kim (MDPI AG, 2019)
Based on the antioxidative effect of resveratrol (RES) in mitigating reactive oxygen species (ROS) production through the induction of nuclear factor-erythroid 2-related factor-2 (Nrf2)/heme oxigenase-1 (HO-1) signaling pathway, we investigated whether the protective activity of RES against ROS-mediated cytotoxicity is mediated by intracellular carbon monoxide (CO), a product of HO-1 activity, in ultraviolet B (UVB)-irradiated human keratinocyte HaCaT cells. The cells were exposed to UVB radiation following treatment with RES and/or CO-releasing molecule-2 (CORM-2). RES and/or CORM-2 upregulated HO-1 protein expression, accompanied by a gradual reduction of UVB-induced intracellular ROS levels. CORM-2 reduced intracellular ROS in the presence of tin protoporphyrin IX, an HO-1 inhibitor, indicating that the cytoprotection observed was mediated by intracellular CO and not by HO-1 itself. Moreover, CORM-2 decreased RES-stimulated mitochondrial quantity and respiration and increased the cytosolic protein expressions of radical-scavenging superoxide dismutases, SOD1 and SOD2. Taken together, our observations suggest that RES and intracellular CO act independently, at least partly, in attenuating cellular oxidative stress by promoting antioxidant enzyme expressions and inhibiting mitochondrial respiration in UVB-exposed keratinocytes.